Investigasi Asal Usul Ayam Indonesia Menggunakan Sekuens Hypervariable-1 D-loop DNA Mitokondria - Syamsul Arifin Zein, Moch; Sulandari, Sri (Jurnal Veteriner; Vol 10 No 1 (2009))
Chicken taxonomy and pedigree investigation are important parts to understand the domesticationprocess occurred on chicken in Indonesia. The Indonesian native chickens have very different clade with thechickens from other Asian countries and others. This study was conducted to construct phylogeny junglefowls (red and green jungle fowls) and Indonesian native chickens, in order to know their relationship.Among the available DNA marker, the region D-loop on DNA mitochondria is the most effective markerused in the investigation. Mitochondrial DNA D-loop (hypervariable-1 segment) was PCR amplified andsubsequently sequenced for a total 33 individuals of green jungle fowls (Gallus varius), 9 individuals of redjungle fowls (Gallus g. gallus) from Indonesia, and 30 individuals of Indonesian native chickens (Lombok,Cemani, Kedu, Kedu Putih, Nunukan, Kate, Pelung, Gaok, Merawang, dan Sentul). Seventy two (72)sequences were used for analysis. Seven (7) published reference D-loop sequences of genus Gallus fromGenBank were also included in the analysis: Gallus varius (GenBank accession number D64163 danD82912), Gallus gallus (GenBank accession number AB098668), G. gallus spadiceus (GenBank accessionnumber AB007721), Gallus gallus bankiva (GenBank accession number AB007718), Gallus lafayetti(GenBank accession number D66893), and Gallus sonneratii (GenBank accession number D66892). Phylogenyanalysis indicates that Indonesia jungle fowls can be grouped into two clades (clades of red jungle fowls/Indonesia native chicken and green jungle fowls). Monophyletic phylogeny trees of jungle fowls from Indonesiawere shown in this study for pedigree investigation of domesticated chickens.
Keywords: Hypervariable-1 segment, DNA mitochondria, Pedigree, investigation, Indonesian Chicken